Relating Environmental and Structural Uncertainty to Management Decision Making Style and Behavior During Information System Planning and Implementation - Singh, Vinay; Sharma, R.R.K.; Lai, K.K. (2020 IEEE International Conference on Industrial Engineering and Engineering Management (IEEM), 2020)
In present study we attempt to relate environmental and structural uncertainties, analysis-paralysis syndrome and organizational politics encountered during Information System Implementation to strategy chosen by Innovators, Prospectors and Defenders. We hypothesized that Innovators and Prospectors type of organizations perceive higher environmental and structural uncertainty than the Defenders type. These uncertainties causes Information System implementation planning "analysis-paralysis" syndrome. As a consequence, these firms are more prone to the employees politicking behaviors. For empirically justification of hypotheses, we collected data from 101 highly experienced executives of 41 business units through structured questionnaire. Statistical result supported our majority of hypotheses.